The Relationship Between PM2.5 and Indoor TVOCs Exposure, Physical Environmental Factors, and Atopy History and allergic Asthma Complaints in 13-14 Years old Children at a Full-Day School in Surabaya - I Dewa Gede Deva Pradnyana Putra; Megara Maritza Tabina; Winarko (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Indoor air pollutants can cause respiratory irritants and trigger allergic asthma complaints, especially in children with a history of atopy. Previous research has found that air pollutants, including PM2.5 and TVOCs, pose risks to respiratory allergy complaints in children. Children spend a significant amount of time at school, so the air quality in classrooms affects their health and productivity. The study was conducted at SMPN 19 Surabaya, located alongside a major road and with a variety of classroom types, potentially exacerbating asthma complaints in children. The research aimed to identify the relationship between exposure to PM2.5, TVOCs, physical environmental factors, and atopy history with asthma complaints in 13-14-year-old children at SMPN 19 Surabaya. Objective: The study aimed to identify the relationship between exposure to PM2.5, TVOCs, physical environmental factors, and atopy history with asthma complaints in 13-14-year-old children at SMPN 19 Surabaya. Method: The research was a quantitative study with an analytical observational design using a cross-sectional approach. The sample size for the study was 69 students aged 13-14 years, selected through purposive sampling from two different characteristic classes, at SMPN 19 Surabaya. An air quality detector was used to measure PM2.5, TVOCs, temperature, and humidity in both classes as well as observe the class's physical condition. Data was collected from student interviews using the ISAAC questionnaire. Data analysis used a bivariate test. Result: The research results showed a relationship between a history of atopy and allergic asthma complaints in children aged 13-14 years in classes 7G and 8A at SMPN 19 Surabaya (p=0.000) and (OR=23.368). However, for indoor pollutant levels PM2.5 (OR= 1.710), TVOCs (OR=1.710), and physical environmental factors such as temperature and humidity did not show a relationship with allergic asthma complaints. Conclusion: It can be concluded that a family history of atopy is associated with asthma complaints in classes at SMPN 19 Surabaya. Therefore, increased awareness and supervision of children with a history of atopy are necessary to prevent or manage potential asthma complaints.